ARMY SYSTEM OF THE BATTLES IN BALI IN THE PHYSICAL REVOLUTION OF THE NICA 1945-1950 - Astika Pidada (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2021)
Cornellis de Houtman is a Dutch sailor who first came to meet the Balinese people. Then followed by the second Dutch visit, namely Cornellis Heemskerck. The purpose of this second visit was to bring Prince Maurits Van Nasau's letter to King Dalem Bekung at the Gelgel palace. The contents of the letter conveyed, namely stating friendship and asking for permission to trade with the king. It turned out that he received permission from Raja Dalem Bekung. In the 19th century this condition changed, the Dutch, who at first declared friendship and asked for permission to trade, instead wanted to control this island. As a result, there was resistance from the kings in Bali, and this resistance continued under the leadership of Lieutenant Colonel I Gusti Ngurah Rai. The weapons used by the fighters in Bali to fight against the Dutch (NICA) were of limited nature both in terms of quality and quantity. The weapons used to fight during the physical revolution in Bali were formerly owned by prayodas, aid from Java, booty belonging to the Dutch (NICA), and made by themselves. The types of weapons that were used by the fighters in Bali during the physical revolution against the Dutch (NICA), such as: Keris, sharpened bamboo, samurai, firecrackers, kitchen ashes, kentongan, yellow iron, bayonet, command knife, keki, stengun, firearms, mortars, hand grenades, carbines, bren, handguns, and heavy submachine guns (12.7). Even though the weapons they had were limited, the Dutch did not dare to underestimate the abilities of the Balinese fighters because they had experience in military education. It is proven that almost every battle was won by Balinese fighters, not a few Dutch soldiers (NICA) died during the physical revolution in Bali. Keywords: NICA; weapons; physical revolution;